Электрооборудование кранов - Богословский А. П. Александр Петрович; Певзнер Е. М. Ефим Маркович; Семерня Н. Ф. Николай Федорович; Шафиров З. Е.; Яуре А. Г. (Москва, Машиностроение, 1983)
Авт. указаны на обороте тит. листа.